Catalyst- and Solvent-Free Stereoselective Addition of Secondary Phosphine Chalcogenides to Alkynes - Artem’ev, Alexander V.; Malysheva, Svetlana F.; Gusarova, Nina K.; Belogorlova, Nataliya A.; Shagun, Vladimir A.; Albanov, Alexander I.; Trofimov, Boris A. (Synthesis, 2015)
The addition of secondary phosphine sulfides and selenides to alkynes proceeds readily (80 °C, 5–13 h) without catalysts or solvents to afford regio- and stereoselectively anti-Markovnikov adducts as tertiary alkenylphosphine chalcogenides of Z-configuration, in 60–94% yield.
Keywords: addition reactions; alkynes; green chemistry; phosphine chalcogenides; regioselectivity